Chemical composition, anti-inflammatory and cytotoxic activities of essential oils from Zanthoxylum myriacanthum Wall. ex Hook. f. fruits, leaves and stems collected in Lam Dong province - Trịnh, Thị Điệp (2024)
Essential oils extracted by hydrodistillation from fruits, leaves, and stems of Z. myriacanthum collected in Bidoup-Nui Ba National Park, Lam Dong province, Vietnam were investigated for their chemical composition and bioactivity. 51 compounds were identified in the fruit oil (ZMFR), of which p-cymen-8-ol (24.9%) and β-pinene (24.3%) were the most abundant. The leaf oil (ZML) contained 32 identified constituents, mainly ρ-methyl-acetophenone (29.9%), α-terpineol (17.0%), ar-curcumene (9.5%), (E)-carpacin (7.7%), 2-undecanone (6.6%) and 2-tridecanone (5.9%). The stem oil (ZMS) consisted of 23 compounds, the major ones being ar-curcumene (44.6%), terpinen-4-ol (13.2%), (1R,2R,4R)-4-(2-hydroxypropan-2-yl)-1-methylcyclohexane-1,2-diol (8.8%) and α-terpineol (8.4%). ZMFR exhibited moderate NO production inhibition in macrophage RAW 264.7 cells with an IC50 value of 42.35 ± 2.63 g/mL. ZMFR and ZML showed moderate cytotoxic effects on SK-LU-1, MCF-7, and HepG2 cancer cell lines with the IC50 values ranging from 50.97 ± 4.07 to 93.78 ± 3.67g/mL. ZMS was cytotoxic against HepG2 (IC50 = 69.84 ± 4.71 g/mL) and MCF-7 (IC50 = 89.28 ± 5.50 g/mL), and showed minimal effect on SK-LU-1. The anti-inflammatory and cytotoxic activities of Z. myriacanthum essential oils were evaluated and reported for the first time.